BMP10 accelerated spinal astrocytic activation in neuropathic pain via ALK2/smad1/5/8 signaling - Jiang Bian; Jiang Bian; Min Luo; Yunyun Tian; Xuejuan Zhang; Bangjian Zhang; Li Yin; Yuehui Zhang (Frontiers in Pharmacology, 2024)
BackgroundAstrocytic activation in the spinal dorsal horn contributes to the central sensitization of neuropathic pain. Bone morphogenetic protein (BMP) 10, one of the BMPs highly expressed in the central nervous system, has been demonstrated to have an accelerated effect on astrocytic activation. This study aimed to investigate the functional effects of BMP10 on the activation of astrocytes in the spinal dorsal horn of animal model of neuropathic pain and to explore potential mechanisms involved in this process.MethodsA neuropathic pain mice model was established using the spared nerve injury (SNI). Western blot analysis was performed to detect the expressional levels of BMP10, activin receptor-like receptor 2 (ALK2), Smad1/5/8, phosphorylated Smad1/5/8, and glial fibrillary acidic protein (GFAP). Immunofluorescence staining was used to detect BMP10, ALK2, and GFAP distribution and expression. The behavioral changes in mice were evaluated using paw withdrawal threshold (PWT), thermal withdrawal latency (TWL), and open field test (OFT). The BMP10 siRNA, Smad1 siRNA, BMP10 peptide, and ALK2-IN-2 (ALK2 inhibitor) were intrathecally administrated to mice. A model of lipopolysaccharide (LPS)-stimulated astrocytes was established to investigate the effect of Smad1. The transfection efficiency of siRNAs was detected by western blot and qRT-PCR analysis.ResultsBMP10 levels were increased in the L4-6 ipsilateral spinal dorsal horn of SNI mice and particularly elevated in astrocytes. Consistently, GFAP and phosphorylated Smad1/5/8 were upregulated in the L4-6 ipsilateral spinal dorsal horn after SNI, indicating the activation of astrocytes and Smad1/5/8 signaling. An intrathecal injection of BMP10 siRNA abrogated pain hypersensitivity and astrocytic activation in SNI mice. In addition, intrathecal administration of BMP10 peptide evoked pain hypersensitivity and astrocytic activation in normal mice, and this action was reversed by inhibiting the ALK2. Furthermore, targeting Smad1 in vitro with the help of siRNA inhibited the activation of astrocytes induced by LPS. Finally, targeting Smad1 abrogated BMP10-induced hypersensitivity and activation of astrocytes.ConclusionThese findings indicate that the BMP10/ALK2/Smad1/5/8 axis plays a key role in pain hypersensitivity after peripheral nerve injury, which indicates its stimulative ability toward astrocytes.